Application of stem-based project-based learning to improve learning outcomes of simple aircraft material - Kristiani, Yulmen; Oktavianty, Erwina; Tiur Maria, Haratua (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study was to determine how well the learning outcomes of students after STEM-based project-based learning on simple aircraft material were used. This study used a quasi-experimental control group design. Quasi experimental design research is a research using experimental classes and control classes. The experimental class and control class will be given a pretest and posttest, the experimental class is a class has treatment that applies STEM-based project-based learning and the control class has treatment using a traditional learning model, namely the lecture and discussion method. The research shows that the use of STEM-based project-based learning and traditional learning can improve student achievement; The use of STEM-based project-based learning is more effective in improving student learning outcomes compared to the use of traditional learning; Student learning outcomes in the experimental class with STEM-based project-based learning are significantly different from student learning outcomes in the control class with traditional learning. It can be said that the learning outcomes for the cognitive component of the class using STEM-based project-based learning.